PENGARUH PIUTANG ANGGOTA DAN SIMPANAN WAJIB TERHADAP PEROLEHAN SHU PADA KOPWAN "LESTARI" DESA PANGKATREJO - Nurus Safa’atillah (Media Mahardhika, 2019)
Given the importance of the development of cooperatives, the task faced by cooperatives for the future more and more severe. Based on the principles and basic joints of cooperatives, one of the requirements to develop the welfare of members in particular and the general public. The cooperative should obtain the advantage or more precisely SHU that will be used as an indicator to assess the success or achievement of the cooperative management in running its business. the method of analysis used in this study is a simple correlation test, multiple linear regression test, multiple correlation test, coefficient of determination test, T test and F test. From multiple linear analysis obtained equation = -5710038,987 + 0,329X1 - 0,510X2, so Account receivable member (X1) is more dominant in effect to the acquisition of SHU (Y) compared with mandatory deposit (X2). The result of hypothesis test t1 (member receivable) 8,272> t table2,571 and t2 (mandatory deposit) -4,835 <t table -2,571 so that member's account and obligatory deposit have partial influence to earnings SHU. F test calculation 181,933> 5,786 so that member account and obligatory deposit have influence simultaneously to acquisition of SHU.